Erratum to: Optimisation of Supercritical Fluid Extraction for Fatty Acids from Benincasa hispida Seed Oil: A Response Surface Approach - Ab Hadi, Hazrina (Journal of Pharmacy, 2026)
Erratum to: Journal of Pharmacy, 5(2), 271-285. The original article can be found here: https://doi.org/10.31436/jop.v5i2.392